2022
DOI: 10.32604/phyton.2022.020790
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Phytochemical Analysis, Nutritional Composition and Antimicrobial Activity of Moringa oleifera

Abstract: Moringa oleifera is a miracle plant rich in nutrients, antioxidants, and antibiotic properties. Present study was designed to evaluate various biochemical attributes of leaves and flowers of M. oleifera. Plant parts (leaves, flowers) of M. oleifera, collected from different roadsides of Multan district, Punjab, Pakistan, were used as experimental material. Result indicates that alkaloids, saponin, carbohydrates, fats, and protein had a high value in the aqueous extract of both leaves and flowers of M. oleifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…However, in the crude fiber value, there is no significant difference between the hot water extraction (6.49±1.18%) and UAE (6.20±0.37%). A previous study reported that crude fiber from Moringa oleifera leaf was about 9.20% (Asghar et al, 2022) and Ficus carica leaf from 6.53% (Teruel-Andreu et al, 2022). The total sugar analyzes by the Phenol-Sulfuric acid method.…”
Section: Total Sugar and Crude Fibermentioning
confidence: 99%
“…However, in the crude fiber value, there is no significant difference between the hot water extraction (6.49±1.18%) and UAE (6.20±0.37%). A previous study reported that crude fiber from Moringa oleifera leaf was about 9.20% (Asghar et al, 2022) and Ficus carica leaf from 6.53% (Teruel-Andreu et al, 2022). The total sugar analyzes by the Phenol-Sulfuric acid method.…”
Section: Total Sugar and Crude Fibermentioning
confidence: 99%
“…The high protein value of M. oleifera leaf extract makes it a good potential source of supplementary protein in functional foods. Moringa oleifera leaves are a respectable source of proteins, which have to be exploited to define their commercial sustainability (Asghar et al, 2022).…”
Section: Proximate Analysis and Phytochemical Screening Of Moringa Ol...mentioning
confidence: 99%
“…There is a need to adopt the use of herbs because these are easily available, minimize the side effects caused by synthetic drugs, and also reduce the cost of drug purchases. Moringa oleifera is a small, fast-growing evergreen or deciduous tree, having soft and white wood with corky and gummy bark and grows up to a height of 12 meters [2].…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that moringa has vitamin C seven times higher than oranges, vitamin A 10 times higher than carrots, calcium 17 times higher than milk [4], protein 9 times higher than yoghurt [4], potassium 15 times higher than bananas [5], and iron 25 times higher than spinach [6]. Moringa's phytochemicals include tannins, sterols, saponins, phenolics, alkaloids, flavonoids (quercetin, isoquercetin, kaempferol, isothiocyanates), and glycosides [2]. M. oleifera possess antispasmodic, expectorant, diuretic and stimulant activities.…”
Section: Introductionmentioning
confidence: 99%